Understanding mangrove conservation through metaphors in ecological discourse: An ecolinguistics study - Muhammad Kiki Kiki Wardana; Dwi Widayati; Mulyadi Mulyadi; Tengku Thyrhaya Zein (Studies in English Language and Education, 2025)
Metaphor is deeply pervasive in human life. It is not only used in aesthetic or literary languages but also in everyday colloquial speech. This study aims to investigate conceptual metaphor in ecological discourse related to mangrove conservation on the eastern coast of North Sumatra and decipher the underlying ecosophy. The researchers also sought to figure out the ecosophical values reflected in the metaphor using an ecolinguistics perspective. A qualitative method was employed to explore the metaphorical expressions concerning mangroves. The data were collected from a report and an interview related to mangrove conservation at Pantai Sejarah Tourism Centre and Mangrove Conservation in Belawan, North Sumatra. The data were analyzed using Steens Metaphor Identification Process (MIP). The results showed that there are 23 instances of conceptual metaphors, categorized into five metaphorical conceptualizations: mangroves are war, mangroves are people, mangroves are a valuable commodity, mangroves are building, and mangroves are containers. These conceptual metaphors have specific linguistic expressions that establish the metaphors. Each metaphor was examined under the lens of ecosophy to determine whether or not the language used promotes the ecosophy. The implications of the study reflect that conceptual metaphors indeed exist in ecological discourse on mangrove conservation, indicating that mangroves are cognitively conceptualized in peoples minds, talked about, and integrated into everyday life.